Visualization and quantification of the degenerative pattern of the talus in unilateral varus ankle osteoarthritis - Seki, Hiroyuki (Sci Rep, 2019)
The aim of this study was to quantify and visualize the degenerative patterns of the talus in ankle osteoarthritis (OA). The differences in talar morphology between sides of patients with unilateral varus ankle OA (medial talar tilt > 4°) were compared. Computed tomography images of both feet of 35 patients (OA: 22 patients, control: 13 patients) were analyzed. Each surface model of the right and left tali was registered to the opposite talus via a mirror-image technique and an iterative closest point algorithm. The surface deviation between the two models was quantified and visualized by deviation color maps. The results quantitatively demonstrated that osteophytes are generated in the area under the antero-medial margin of the trochlea in OA tali. In severe OA tali, bone resorption of more than 2 mm in the medial portion of the trochlea, as well as a similar degree of osteophyte formation on the lateral surface, was also seen. Stereotypical patterns of degeneration occurring in OA tali were successfully visualized and quantified by left-right comparison of patients with unilateral ankle OA. Such information would contribute to better understanding of the development of ankle OA and preoperative planning of total ankle arthroplasty and arthrodesis.